A quantitative topological descriptor for linear co-oligomer fusion. Issue 52 (14th June 2018) - Koskin, Igor P.; Mostovich, Evgeny A.; Benassi, Enrico; Kazantsev, Maxim S.
Abstract : A purely topological descriptor allows quantitative correlation of the fusion degree with optoelectronic performance. Abstract : A purely topological descriptor for the quantitative classification of fully or partially fused linear quasi-one dimensional centre-symmetric molecules is proposed. The index also makes it possible to quantitatively correlate optoelectronic properties with the molecular topology without involving an explicit calculation of the molecular electronic structure.